Investigating the effects of counseling programs on runaway youth - Mohammad Reza Iravani; Hossein Ebrhaimzadeh Asmin (Management Science Letters)
This paper presents an empirical investigation to study the effects of counseling programs on reducing the runaway youth in Iran. The study selects a sample of 30 students and divides them into two groups of control and experiment. The first group is kept under eight sessions of social skills training and a questionnaire consists of various questions including confidence items is distributed among both groups after the training ends. The implementation of Kolmogorov-Smirnov has revealed that both pre and post-test data are normally distributed. In addition, the result of ANOVA test has revealed that training program could significantly improve runaway youth’s confidence.